Factor Influencing Sustainability Reporting Assurance: A Study of Indonesian Public Listed Companies - Utami, Riescha; Ameraldo, Fedi; Fella Rizki, Marsi; Jihad Rabaya, Abdullah (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: In the era of globalization, companies are evaluated not only on their financial performance but also on their social and environmental impact. Specific Background: Sustainability reporting serves as a critical medium for communicating a company's efforts to achieve its sustainability objectives, mitigating its negative impacts on society and the environment, and fostering trust. The Global Reporting Initiative (GRI) is widely regarded as the standard for these reports, enhancing their credibility. Knowledge Gap: While previous studies have largely focused on major multinational companies, there is limited research on the assurance of sustainability reports within the context of developing economies, particularly Indonesia. Aims: This study aims to examine the effects of the sustainability committee, industry type, and awards on sustainability reporting assurance among companies listed on the Indonesia Stock Exchange in 2022. Results: Logistic regression analysis reveals that both sustainability committees and awards positively influence sustainability reporting assurance, whereas industry type shows no significant impact. Novelty: This research fills a gap by analyzing sustainability assurance practices within Indonesia, providing insights into the factors influencing assurance in emerging markets. Implications: The findings suggest that sustainability committees and awards can enhance reporting assurance, thereby boosting stakeholder confidence in corporate sustainability practices. This underscores the importance of establishing effective sustainability governance structures and recognizing exemplary efforts to drive transparency and accountability in sustainability reporting.